Linezolid-induced black hairy tongue: A case report and review of literature - Moin A Siddiqui; Mohammad Adil; Syed S Amin; Kritika Xess (Wolters Kluwer Medknow Publications, 2022)
Black hairy tongue is an asymptomatic and benign condition presenting with black-to-brownish discoloration of the dorsum of the tongue with elongated filiform papillae. Several medications, particularly antibiotics, are implicated in its causation. Xerostomia, abnormal desquamation of the tongue, use of oxidizing mouthwashes, excessive intake of nicotine, coffee, and tea, and immunosuppressive states predispose to the development of this condition. Herein, we describe a case of a young female who developed black hairy tongue within 5 days of linezolid intake. The discoloration disappeared after 7 days of stopping the drug. We also summarize the various reports of black hairy tongue due to linezolid in a tabular form. We aim to highlight the importance of medication history in the identification of this uncommon condition. We also emphasize identifying risk factors for this condition and educating the patients about them.